Electoral Campaigns, Media, and the New World of Digital Politics - Davis, Richard, 1955-; Taras, David, 1950- (Book collections on Project MUSE., 2022)
Today, political leaders and candidates for office must campaign in a multi-media world not only through the traditional media forums - newspapers, radio, and television - but also through new digital media, particularly social media. Electoral Campaigns, Media, and the New World of Digital Politics chronicles how Twitter, Facebook, Reddit, email, and memes are used successfully and unsuccessfully to influence elections. Each of these platforms have different affordances and reach different audiences in different ways and campaigns often have to wage different campaigns on each of these mediums. In some instances, they are crucial in altering coverage in the mainstream media. In others, digital media remains under-utilized and undeveloped. As has always been the case in politics, outcomes that depend on economic and social conditions often dictate people's readiness for certain messages. However, the method and content of those messages has changed with great consequences for the health and future of democracy. This book answers several questions: How do candidates/parties reach audiences that are preoccupied, inattentive, amorphous and bombarded with so many other messages? How do they cope with the speed of media reporting in a continuous news cycle that demands instantaneous responses? How has media fragmentation altered the campaign styles and content of campaign communication, and general campaign discourse? Finally and most critically, what does this mean for how democracies function?